Pride and Competency in Accelerated Nursing Programs. Issue 6 (November 2018) - Tornwall, Joni; Tan, Alai; Bowles, Wendy
Abstract: AIM: The aim of this study was to examine student-level and school-level variation in pride and competency in accelerated nursing programs and the relationship between student satisfaction with instructional methods and perceptions of pride and competency. BACKGROUND: Nursing students in accelerated, second-degree programs have a greater need to feel competent when compared to traditionally educated nurses; however, evidence to illuminate a relationship between faculty instructional methods and student pride and competency is lacking. METHOD: The method was a secondary analysis of data collected from 3, 506 students in 130 programs over seven years. RESULTS: Higher levels of satisfaction with instructional methods were associated with higher levels of pride and competency in nursing skills. There was no significant variation in pride and competency in nursing skills across institutions. CONCLUSION: Student satisfaction with instructional methods in accelerated nursing education has an impact on student pride and competency.